A Cassette Containing Thiostrepton, Gentamicin Resistance Genes, and dif sequences Is Effective in Construction of Recombinant Mycobacteria - Mugweru, Julius; Makafe, Gaelle; Cao, Yuanyuan; Zhang, Yang; Wang, Bangxing; Huang, Shaobo; Njire, Moses; Chhotaray, Chiranjibi; Tan, Yaoju; Li, Xinjie; Liu, Jianxiong; Tan, Shouyong; et al. (Frontiers in Microbiology, 2017)
The genetic manipulation of Mycobacterium tuberculosis genome is limited by the availability of selection markers. Spontaneous resistance mutation rate of M. tuberculosis to the widely used kanamycin is relatively high which often leads to some false positive transformants. Due to the few available markers we have created a cassette containing thiostrepton resistance gene (tsr) for selection in M. tuberculosis and M. bovis BCG, and gentamicin resistance gene (aacC1) for E.coli and M. smegmatis mc2155, flanked with dif sequences recognized by the Xer system of mycobacteria. This cassette adds to the limited available selection markers for mycobacteria.